Gambaran Penggunaan Antipsikotik Terhadap Pasien Skizofrenia di Rumah Sakit Kota Indramayu - Suzana, Dona; Febriyani, Ayu (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Schizophrenia is a psychiatric disorder characterized by disturbances in thinking processes, perceptions, emotional responses, and social interactions. The therapy commonly used in the treatment of schizophrenia is antipsychotic or psychotropic drugs. The use of psychotropic drugs is the first step in overcoming and following up on mental disorders. The object of this research is several hospitals that treat patients with psychiatric disorders, namely schizophrenia. Where the subjects used in this study were men/women with schizophrenia aged 18 to 60 years in the city of Indramayu who are undergoing treatment at the hospital for the 2020-2022 period. This study aims to describe the use of antipsychotic classes that are used as one of the pharmacological therapies in patients. This research method uses a descriptive quantitative method, while the sample fee used in this study is the slovin calculation formula, with a total population of 875 and a sample of 274 is obtained. The results obtained are based on the proportion of sex, mostly male patients (62.4%), the highest proportion of the age range was found in early adulthood (70.8%), the highest diagnosis was YTT schizophrenia (46%). Then patients with a history of not going to school (63.5%) and a history of not working (88.3%). Most of the data obtained were patients who experienced mild recurrence of 62%. As for the large number of patient histories with mild or insignificant recurrence, this can influence the factors supporting the success of treatment, namely the use of insurance. This opinion was obtained from patient payment status data, in which the most widely used payment status was the use of insurance by 82.1%. In data on the use of the single antipsychotic that is most widely used in each type of schizophrenia is the antipsychotic haloperidol and the combination that is most widely used is haloperidol-chlorpromazine